Information Transfer Materials For Interested Publics: A Survey Of Water Resources Research Institutes - Nick Houtman (Journal of Applied Communications, 1991)
Water Resources Research Institutes (WWRIs) have traditionally targeted technical audiences with information transfer efforts, but non-technical audiences also play a role in decision-making.